Існуючі методики діагностики та підходи до оцінювання рівня розвитку корпоративної культури підприємств - Чернух, Д.В. (Економічний вісник Донбасу, 2023)
В умовах формування ринкових відносин, посилення конкуренції, глобалізації та інтеграції України в ЄС, підприємства змушені постійно еволюціонувати й швидко реагувати на зміни. Рушійною силою в цих процесах виступає корпоративна культура, яка обʼєднує підприємство та персонал єдиною місією, єдиною філософією, стратегією розвитку, принципами, цінностями, традиціями, створює репутацію в діловому світі, формує імідж організації, підвищує її конкурентоспроможність і забезпечує конкурентну перевагу.
Для досягнення поставленої мети були використані різні методи дослідження, такі як порівняльний аналіз, системного підходу, структурного аналізу, факторного аналізу, методу синтезу, формалізації, структурно-логічного узагальнення.
Метою наукової роботи є теоретичне узагальнення методів діагностики, оцінювання й аналізу корпоративної культури та обґрунтування методичного підходу до її оцінки.
Зокрема у науковій роботі досліджено: різноманіття підходів та методів оцінювання культури, в основу яких покладено різні способи діагностики, параметри і складові корпоративної культури та методи представлення результатів. Виділено переваги та недоліки якісних та кількісних методів оцінювання корпоративної культури.
Досліджено та узагальнено основні методологічні підходи до дослідження організаційної культури. Зʼясовано, що сьогодні вчені надають перевагу кількісним методам оцінювання, які дають можливість дослідити достатньо велику кількість організацій і дати формалізований опис притаманних їх корпоративної культури.
Виявлено, що діагностика корпоративної культури повинна ґрунтуватись на таких методологічних принципах, як: науковість (використання досягнень наукових дисциплін, які мають своїм об’єктом людину, організації, працю); системність у сприйнятті об’єктів дослідження та управління; професіоналізм, що передбачає наявність у дослідника специфічного досвіду та навичок; визнання підприємства як частини суспільства; гуманізм, що базується на визнанні індивідуума найвищою цінністю.
Проведено аналіз методик оцінювання корпоративної культури іноземними та українськими науковцями, виокремлено їх переваги та недоліки. Та зʼясовано, що сьогодні немає єдиного підходу до оцінювання корпоративної культури підприємства. In the context of the formation of market relations, the strengthening of competition, globalization, and Ukraine's integration into the EU, enterprises are forced to constantly evolve and quickly respond to changes. The driving force in these processes is corporate culture, which unites the enterprise and staff with a single mission, a single philosophy, a development strategy, principles, values, traditions, creates a reputation in the business world, shapes the organization's image, increases its competitiveness, and provides a competitive advantage.
To achieve the set goal, various research methods were used, such as comparative analysis, systems approach, structural analysis, factor analysis, synthesis method, formalization, and structural-logical generalization.
The purpose of the research is to theoretically summarize the methods of diagnostics, evaluation, and analysis of corporate culture and to substantiate a methodological approach to its assessment.
In particular, the research paper investigates: the diversity of approaches and methods for assessing organizational culture, which are based on different diagnostic methods, parameters and components of corporate culture, and methods for presenting results. The advantages and disadvantages of qualitative and quantitative methods for assessing corporate culture are identified.
The main methodological approaches to the study of organizational culture are investigated and summarized. It was found that today scientists prefer quantitative methods of assessment, which make it possible to study a sufficiently large number of organizations and give a formalized description of their corporate culture.
It was revealed that the diagnostics of corporate culture should be based on the following methodological principles: Scientificity (the use of the achievements of scientific disciplines that have a person, organization, and work as their object); Systematicity in the perception of objects of research and management; Professionalism, which implies the presence of specific experience and skills in the researcher; Recognition of the enterprise as part of society; Humanism, which is based on the recognition of the individual as the highest value.
An analysis of methods for assessing corporate culture by foreign and Ukrainian scientists was conducted, their advantages and disadvantages were identified. It was found that today there is no single approach to assessing the corporate culture of an enterprise.
It was analyzed that each of the mentioned approaches makes it possible to carry out only the diagnostics of the corporate culture of the enterprise, but does not fully take into account the practice of functioning of economic entities, including domestic ones.
It was investigated and analyzed that European and American researchers, for the assessment of the corporate culture of the enterprise, first of all, take into account the personal characteristics of the personnel. On the other hand, in the works of domestic scientists, it is stated that the diagnostics of the corporate culture of the enterprise should be carried out according to indicators that directly affect the efficiency of the enterprise.
It was found that the main purpose of corporate culture diagnostics is the systematic interpretation of existing cultural symptoms using certain tools, and the result is the visualization of the existing corporate culture.